Biology and christian ethics. - Clark, Stephen R. L.. (Cambridge Cambridge University press, 2000)
Professor Clark takes a reasoned look at biological theory since Darwin and argues that an orthodox Christian philosophy is better able to accommodate the truth of such theory than is the sort of progressive, meliorist interpretation of Christian doctrine which is usually offered as the properly modern option. (CUP)
Keywords: Biology -- Religious aspects&delete& -- Christianity; Christian ethics; Ethics, Evolutionary; 241.63*5 -- Theologische ethiek: bio-ethiek (bioethiek); genetische experimenten; transplantatie; eugenetica